Widespread occurrence of pink salmon (Oncorhynchus gorbuscha) throughout Greenland coastal waters. Issue 6 (24th March 2020) - Nielsen, Julius; Rosing‐Asvid, Aqqalu; Meire, Lorenz; Nygaard, Rasmus
Abstract: Using social media, the Greenland Institute of Natural Resources collected data on the occurrence of pink salmon ( Oncorhynchus gorbuscha ) in 2019. Eighty‐four pink salmon were reported from 22 locations across Greenland. This comprised 76 specimens from 2019 and 8 specimens from 2013 to 2018. Of these, 12 were caught in fresh water, and a single pink salmon was from the bottom of the Nuuk Fjord near the Kapisillit River – the only known river in Greenland where the Atlantic salmon ( Salmo salar ) spawn. It is unknown if pink salmon have reproduced in Greenland waters.